X-Git-Url: http://matita.cs.unibo.it/gitweb/?a=blobdiff_plain;f=helm%2Fsoftware%2Fmatita%2Flibrary%2Fdemo%2Fpower_derivative.ma;h=a425dfcc357783ee52a23f8215be3d91265d29b5;hb=5431da8145e4a84596d312fc02b552881d119100;hp=10cb21835790765e9e7fe64e39bd5b3f862251fb;hpb=7cb22a7f8107a6cde0b77b7879e04f586a347102;p=helm.git diff --git a/helm/software/matita/library/demo/power_derivative.ma b/helm/software/matita/library/demo/power_derivative.ma index 10cb21835..a425dfcc3 100644 --- a/helm/software/matita/library/demo/power_derivative.ma +++ b/helm/software/matita/library/demo/power_derivative.ma @@ -209,40 +209,45 @@ for @{ 'derivative $f }. interpretation "Rderivative" 'derivative f = (derivative f). -notation "hvbox('x' \sup n)" +(* FG: we definitely do not want 'x' as a keyward! + * Any file that includes this one can not use 'x' as an identifier + *) +notation "hvbox('X' \sup n)" non associative with precedence 60 for @{ 'monomio $n }. -notation "hvbox('x')" +notation "hvbox('X')" non associative with precedence 60 for @{ 'monomio 1 }. interpretation "Rmonomio" 'monomio n = (monomio n). -axiom derivative_x0: D[x \sup 0] = 0. -axiom derivative_x1: D[x] = 1. +axiom derivative_x0: D[X \sup 0] = 0. +axiom derivative_x1: D[X] = 1. + axiom derivative_mult: ∀f,g:R→R. D[f·g] = D[f]·g + f·D[g]. alias symbol "middot" = "Fmult". -theorem derivative_power: ∀n:nat. D[x \sup n] = n·x \sup (pred n). +theorem derivative_power: ∀n:nat. D[X \sup n] = n·X \sup (pred n). assume n:nat. (*we proceed by induction on n to prove - (D[x \sup n] = n · x \sup (pred n)).*) + (D[X \sup n] = n · X \sup (pred n)).*) elim n 0. case O. - the thesis becomes (D[x \sup 0] = 0·x \sup (pred 0)). + the thesis becomes (D[X \sup 0] = 0·X \sup (pred 0)). done. case S (m:nat). by induction hypothesis we know - (D[x \sup m] = m·x \sup (pred m)) (H). + (D[X \sup m] = m·X \sup (pred m)) (H). the thesis becomes - (D[x \sup (1+m)] = (1+m) · x \sup m). + (D[X \sup (1+m)] = (1+m) · X \sup m). we need to prove - (m · (x \sup (1+ pred m)) = m · x \sup m) (Ppred). + (m · (X \sup (1+ pred m)) = m · X \sup m) (Ppred). + lapply depth=0 le_n; we proved (0 < m ∨ 0=m) (cases). we proceed by induction on cases - to prove (m · (x \sup (1+ pred m)) = m · x \sup m). + to prove (m · (X \sup (1+ pred m)) = m · X \sup m). case left. suppose (0 < m) (m_pos). using (S_pred ? m_pos) we proved (m = 1 + pred m) (H1). @@ -251,13 +256,16 @@ theorem derivative_power: ∀n:nat. D[x \sup n] = n·x \sup (pred n). suppose (0=m) (m_zero). by m_zero, Fmult_zero_f done. conclude - (D[x \sup (1+m)]) - = (D[x · x \sup m]). - = (D[x] · x \sup m + x · D[x \sup m]). - = (x \sup m + x · (m · x \sup (pred m))) timeout=30. - = (x \sup m + m · (x \sup (1 + pred m))). - = (x \sup m + m · x \sup m). - = ((1+m) · x \sup m) timeout=30 by Fmult_one_f, Fmult_commutative, Fmult_Fplus_distr, costante_sum + (D[X \sup (1+m)]) + = (D[X · X \sup m]). + = (D[X] · X \sup m + X · D[X \sup m]). + = (X \sup m + X · (m · X \sup (pred m))). + lapply depth=0 Fmult_associative; + lapply depth=0 Fmult_commutative; + = (X \sup m + m · (X · X \sup (pred m))) by Fmult_associative, Fmult_commutative. + = (X \sup m + m · (X \sup (1 + pred m))). + = (X \sup m + m · X \sup m). + = ((1+m) · X \sup m) by Fmult_one_f, Fmult_commutative, Fmult_Fplus_distr, costante_sum done. qed. @@ -271,30 +279,30 @@ for @{ 'derivative ${default interpretation "Rderivative" 'derivative \eta.f = (derivative f). *) -notation "hvbox(\frac 'd' ('d' 'x') break p)" with precedence 90 +notation "hvbox(\frac 'd' ('d' 'X') break p)" with precedence 90 for @{ 'derivative $p}. interpretation "Rderivative" 'derivative f = (derivative f). -theorem derivative_power': ∀n:nat. D[x \sup (1+n)] = (1+n) · x \sup n. +theorem derivative_power': ∀n:nat. D[X \sup (1+n)] = (1+n) · X \sup n. assume n:nat. (*we proceed by induction on n to prove - (D[x \sup (1+n)] = (1+n) · x \sup n).*) elim n 0. + (D[X \sup (1+n)] = (1+n) · X \sup n).*) elim n 0. case O. - the thesis becomes (D[x \sup 1] = 1 · x \sup 0). + the thesis becomes (D[X \sup 1] = 1 · X \sup 0). done. case S (m:nat). by induction hypothesis we know - (D[x \sup (1+m)] = (1+m) · x \sup m) (H). + (D[X \sup (1+m)] = (1+m) · X \sup m) (H). the thesis becomes - (D[x \sup (2+m)] = (2+m) · x \sup (1+m)). + (D[X \sup (2+m)] = (2+m) · X \sup (1+m)). conclude - (D[x \sup (2+m)]) - = (D[x · x \sup (1+m)]). - = (D[x] · x \sup (1+m) + x · D[x \sup (1+m)]). - = (x \sup (1+m) + x · (costante (1+m) · x \sup m)). - = (x \sup (1+m) + costante (1+m) · x \sup (1+m)). - = ((2+m) · x \sup (1+m)) timeout=30 by Fmult_one_f, Fmult_commutative, + (D[X \sup (2+m)]) + = (D[X · X \sup (1+m)]). + = (D[X] · X \sup (1+m) + X · D[X \sup (1+m)]). + = (X \sup (1+m) + X · (costante (1+m) · X \sup m)). + = (X \sup (1+m) + costante (1+m) · X \sup (1+m)). + = ((2+m) · X \sup (1+m)) timeout=30 by Fmult_one_f, Fmult_commutative, Fmult_Fplus_distr, assoc_plus, plus_n_SO, costante_sum done. qed.